Comparison of lipooligosaccharides from human challenge strains of Neisseria gonorrhoeae - John, Constance M.; Phillips, Nancy J.; Cardenas, Amaris J.; Criss, Alison K.; Jarvis, Gary A. (Frontiers in Microbiology, 2023)
The alarming rise of antibiotic resistance and emergence of new vaccine technologies have increased the focus on vaccination to control gonorrhea. FA1090 and MS11 are strains of Neisseria gonorrhoeae that have been used in challenge studies in human males. We used negative-ion MALDI-TOF MS to profile intact lipooligosaccharide (LOS) from strains MS11mkA, MS11mkC, FA1090 A23a, and FA1090 1-81-S2. The MS11mkC and 1-81-S2 variants were isolated from male volunteers infected with MS11mkA and A23a, respectively. LOS profiles were obtained after purification by the classical phenol water extraction method and by microwave-enhanced enzymatic digestion, which is more amenable for small scale work. Despite detecting some differences in the LOS profiles, the same major species were observed indicating that the microwave-enhanced enzymatic digestion is appropriate for MS studies. The compositions determined for MS11mkA and mkC LOS were consistent with previous reports. FA1090 is strongly recognized by mAb 2C7, an antibody binding LOS with both αand β-chains if the latter is a lactosyl group. Spectra of the A23a and 1-81-S2 FA1090 LOS were similar to each other and consistent with expression of α-chain lacto-N-neotetraose and β-chain lactosyl moieties that can both be accepter sites for sialic acid substitution. 1-81-S2 LOS was analyzed after culture with and without media supplemented with cytidine-5'monophosphate N-acetylneuraminic acid (CMP-Neu5Ac) that N. gonorrhoeae needs to sialylate its LOS. LOS sialylation reduces infectivity of gonococci in men, although it induces serum resistance in serum-sensitive strains and reduces killing by neutrophils and antimicrobial peptides. Infectivity of FA1090 in men is much lower than that of MS11mkC but the reason for this difference is unclear. Interestingly, some peaks in the spectra of 1-81-S2 LOS after bacterial culture with CMP-Neu5Ac were consistent with disialylation of the LOS, which could be relevant to the reduced infectivity of FA1090 in men and could have implications regarding the phase variation of the LOS and the natural history of infection.